Large scale geodetic projects in Republic of Macedonia - Zlatko Srbinoski; Zlatko Bogdanovski; Sashe Dimeski (International Scientific Conference GEO 2016 and XXIX Meeting of Serbian surveyors, 2016)
In this paper are shown the basic characteristics of large scale geodetic and cartographic projects in Republic of Macedonia. The past decade in the Republic of Macedonia was full of realization of major projects in the area of geodesy and cartography. These projects, which will be discussed in this paper are related with improvement of geodetic and cadastral system, development of new topographic maps, establishment of basic geodetic networks, as well as projects related to the implementation of the National Spatial Data Infrastructure (NSDI) - in line with European trends and INSPIRE directives
Keywords: national geodetic projects, topographic maps, basic geodetic networks